Hydrodeoxygenation of m-Cresol over Ru based catalysts: Influence of catalyst support on m-Cresol conversion and methylcyclohexane selectivity. (May 2020) - Kumar, Adarsh; Kumar, Avnish; Biswas, Bijoy; Kumar, Jitendra; Yenumala, Sudhakara Reddy; Bhaskar, Thallada
Abstract: The hydrodeoxygenation (HDO) of m-Cresol (a representative of lignin bio-oil) has enormous potential for the production of valuable compounds. The products obtained from HDO of m-Cresol (m-Cr) are blendable into conventional fuels and essential for chemical industries such as plastic, fiber, rubber, resin, film, and coating industry. Ruthenium loaded acidic supports (ZSM-5, β-zeolite, y-zeolite, mordenite, COK12, ZrO2, TiO2 ) were used for the selective hydrodeoxygenation of m-Cresol into methylcyclohexane (MCXane). The effects of acid sites, as well as the pore size of the different supports on the hydrodeoxygenation activity and selectivity towards methylcyclohexane were addressed. The methylcyclohexane yield increased with increasing number of acid sites up to optimum acidity (532 μmol/gm) along with pore size (5.9 A o ). The experiments were carried out at 225–325 °C and 1–40 bar hydrogen pressure in a fixed bed reactor and observed that reaction temperature, and hydrogen pressure promoted the hydrodeoxygenation. The Ru/ZSM-5 is a stable (240 h) catalyst and displayed excellent behavior in both hydrodeoxygenation activity (100%) and methylcyclohexane selectivity (100%) for m-Cresol. Graphical abstract: Image 1 Highlights: 1 wt % Ru incorporated various acidic catalytic systems tested for m-Cresol HDO. Ru/ZSM-5 is best catalyst for selective production of MCXane (100%) with 240 h life and up to 4 cycles. Pore size (5.9 A o ) and high acidity (532 μmol/gm) of Ru/ZSM-5 are key factors for MCXane selectivity. High hydrogen pressure favours the Caromatic -OH cleavage but preserve Caromatic -CH3 bond.